Global trends and performance of dry needling from 2004 to 2024: a bibliometric analysis - Wang, Min; Zhao, Tianci; Liu, Jiaxin; Luo, Shouyang (Frontiers in Neurology, 2024)
Background Many doctors are incorporating dry needling into their clinical practice. Despite this growing trend, there has not been a comprehensive bibliometric analysis conducted in this field. Thus, this study aims to investigate the current research landscape, key research contributors, and popular research topics in dry needling, and to analyze the developmental trends within this area of study. Methods The study utilized the Web of Science Core Collection (WoSCC) as the main data source. Scientific literature was gathered through title (TI) searches for original clinical research papers on dry needling published between 2004 and 2024, using ‘dry needling’ or ‘dry needle’ as the search term. Statistical analyses and visualizations of the literature information, such as keywords, countries, research institutions, and authors, were conducted using the bibliometric.com online platform and VOSviewer. This approach aimed to statistically analyze and visualize the key research entities, hotspots, and frontiers in dry needling research. Additionally, the study delved into collaborative networks, research outputs, hot topics, and trends within the field of dry needling. Results This investigation encompassed 468 publications, with the year 2021 topping the charts for the highest publication output, amassing a total of 271 articles. The journal “Acupuncture in Medicine” emerged as the most frequently cited publication. The most impactful article was titled “Acupuncture and dry-needling for low back pain: An updated systematic review within the framework of the Cochrane Collaboration.” Spain took the lead as the most productive country in this domain, with the United States closely following. Cesar Fernández-de-las-Peñas emerged as the most prolific author in the field. The Universidad Rey Juan Carlos in Spain was recognized as the most productive institution for research in dry needling. As for journal keywords, “dry needling,” “trigger point,” and “myofascial pain syn-drome” were the triumvirate of terms most recurrently encountered. Conclusion The field of dry needling research has witnessed significant growth in recent years, characterized by the emergence of novel trends such as comparative studies with acupuncture, exploration into the mechanisms of action, and a transition toward interdisciplinary approaches. As medical models evolve, the focus is expanding from the exclusive treatment of muscle pain to broader applications. Despite this progress, the domain is underscored by a paucity of large-scale, multicenter clinical trials and animal studies. There exists an imperative for enhanced collaboration among academic and research institutions. A more profound exploration and comprehensive research endeavors are essential to enhance our understanding and broaden the clinical application of dry needling techniques.